2022
DOI: 10.1097/nor.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Constipation Incidence and Effects of Selected Risk Factors on Constipation Development in Elderly Patients With Hip Fracture

Abstract: Constipation is a common problem in the general population and is particularly prevalent among hospitalized elderly patients with hip fracture due to lack of mobility, medications, and lack of privacy associated with hospitalization. This study aimed to determine the incidence of postoperative constipation and the effects of selected risk factors on constipation development in elderly patients with hip fracture. The study used a descriptive, cross-sectional, and prospective design. Data were collected on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…. this finding was supported by (Celik B and Bilik Ö 2022) (29) observation which include more than three quarters of patient with hip fracture developed constipation . Also this result agreed with Jing D, Jia L ,2019) (30) who stated that the majority of studied patient had constipation postoperatively in their study .…”
Section: Discussionmentioning
confidence: 55%
“…. this finding was supported by (Celik B and Bilik Ö 2022) (29) observation which include more than three quarters of patient with hip fracture developed constipation . Also this result agreed with Jing D, Jia L ,2019) (30) who stated that the majority of studied patient had constipation postoperatively in their study .…”
Section: Discussionmentioning
confidence: 55%
“…The results of this study also showed that psychological or behavioral barriers to defecation in the hospital environment were a risk factor for postoperative constipation in patients undergoing cardiovascular surgery. It included decreased appetite, decreased mobility, increased stress, and not being adapted to the hospital environment [14]. Defecation requires a private and comfortable environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the hospital stay of heart surgery patients generally does not exceed 20 days, therefore we adopted the North America Nursing Diagnosis Association general definition of constipation, which is the state in which an individual experiences or is at high risk of experiencing stasis of the large intestine, resulting in infrequent elimination and/or the inability to achieve a soft bowel movement, a feeling of incomplete rectal emptying, the need for manual evacuation of the rectal region [13]. A re-established defecation pattern was defined as the absence of defecation for 3 days or longer, without the use of any laxative or specific methods to facilitate evacuation [14]. Patients' constipation risk was evaluated from the second postoperative day and upon discharge in this study.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation